Contractual Structure and Wealth Accumulation - Mookherjee, Dilip; Ray, Debraj (American Economic Review, 2002)
Can historical wealth distributions affect long-run output and inequality despite “rational” saving, convex technology and no externalities? We consider a model of equilibrium short-period financial contracts, where poor agents face credit constraints owing to moral hazard and limited liability. If agents have no bargaining power, poor agents have no incentive to save: poverty traps emerge and agents are polarized into two classes, with no interclass mobility. If instead agents have all the bargaining power, strong saving incentives are generated: the wealth of poor and rich agents alike drift upward indefinitely and “history” does not matter eventually.